2012
DOI: 10.1016/j.bbamem.2011.07.045
|View full text |Cite
|
Sign up to set email alerts
|

Water wires in atomistic models of the Hv1 proton channel

Abstract: The voltage-gated proton channel (Hv1) is homologous to the voltage-sensing domain (VSD) of voltage-gated potassium (Kv) channels but lacks a separate pore domain. The Hv1 monomer has dual functions: it gates the proton current and also serves as the proton conduction pathway. To gain insight into the structure and dynamics of the yet unresolved proton permeation pathway, we performed all-atom molecular dynamics simulations of two different Hv1 homology models in a lipid bilayer in excess water. The structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
123
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(128 citation statements)
references
References 69 publications
3
123
2
Order By: Relevance
“…The sequence similarity between Hv1 and the VSD of Kv1.2 is very limited, which makes it difficult to generate a homology model based only on sequence alignment, especially for the positioning of the three arginines in the S4 segment of Hv1 (10,11,22). Three other groups have proposed structural models of the open state of Hv1 channel.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The sequence similarity between Hv1 and the VSD of Kv1.2 is very limited, which makes it difficult to generate a homology model based only on sequence alignment, especially for the positioning of the three arginines in the S4 segment of Hv1 (10,11,22). Three other groups have proposed structural models of the open state of Hv1 channel.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the continuous aqueous pathway in this model might be caused by the farther outward positioning of the S4 segment. Wood et al (11) suggested two different open-state models (R1-Hv1 and R2-Hv1) with different S4 alignments (Fig. S8 C and D).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations